2008
DOI: 10.1007/s10714-008-0651-3
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory behaviour of closed isotropic models in second order gravity theory

Abstract: Homogeneous and isotropic models are studied in the Jordan frame of the second order gravity theory. The late time evolution of the models is analysed with the methods of the dynamical systems. The normal form of the dynamical system has periodic solutions for a large set of initial conditions. This implies that an initially expanding closed isotropic universe may exhibit oscillatory behaviour.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…In view of the above interpretation, it is easy to check that substituting fðRÞ ¼ R þ R 2 in (1) with à ¼ 0, the scalar curvature takes the constant value given by (3), exactly as was shown in Ref. [3].…”
supporting
confidence: 55%
See 2 more Smart Citations
“…In view of the above interpretation, it is easy to check that substituting fðRÞ ¼ R þ R 2 in (1) with à ¼ 0, the scalar curvature takes the constant value given by (3), exactly as was shown in Ref. [3].…”
supporting
confidence: 55%
“…However, in a previous investigation it was found that this is not the case [3]. More precisely, without making use of expansionnormalized variables it is shown in Ref.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Moreover, Kasner solutions are "building blocks" for BKL chaotic approach to a singularity in more general models like Bianchi IX mode [40]l. The study of asymptotic solutions in quadratic gravity was previously addressed, for example, by [41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…If the equation of state parameter γ < 1, the smooth part of solution coincides with GR behaviour, otherwise the influence of quadratic curvature correction becomes important at late times (see [35,36]). …”
Section: Introductionmentioning
confidence: 99%